Theoretical and experimental investigation of external-stress effect on quantum-well-based semiconductor interferometer performance. (16th August 2021) - Ueda, Yuta; Hashizume, Yasuaki; Yamada, Takashi; Matsuzaki, Hideaki; Ishikawa, Mitsuteru
Abstract: We investigate characteristic fluctuations in multi-quantum well (MQW)-based waveguides whose absorption spectrum experimentally changes as a ∼5 nm blue shift when dielectric passivation layers are employed. We theoretically show that the blue shift corresponds to a ∼0.03% compressive strain in the MQW resulting in a group refractive index change (Δ n g ) of ∼−0.01. The estimated Δ n g agrees with an experimentally obtained free spectral range of transmittance of an asymmetric Mach–Zehnder interferometer composed of the MQW structure. The results indicate that our theoretical estimation is an efficient way to evaluate the MQW-based waveguide performance with an external stress.